Isotopic Nd compositions and concentrations of the lithogenic inputs into the ocean: A compilation, with an emphasis on the margins - Jeandel, C.; Arsouze, T.; Lacan, F.; Téchiné, P.; Dutay, J.-C. (Chemical geology, 2007)
An extensive compilation of published Nd isotopic values has been made in order to establish a database and a map of the isotopic composition of Nd of the world coasts. Both the database and the map are set out here, together with the way we interpolated the data to make the map. The margin Nd isotopic signatures vary from non-radiogenic values around the Atlantic Ocean to radiogenic values around the Pacific consistent with the trajectory of the “conveyor belt” global circulation, reinforcing the hypothesis that the exchange of Nd along the margins could play a significant role in driving the oceanic distribution of this tracer.